Fractional microneedle radiofrequency versus fractional carbon dioxide laser in the treatment of postburn hypertrophic scars. Issue 8 (28th July 2022) - Tawfic, Shereen O.; Hassan, Akmal S.; El‐Zahraa SH Aly, Fatma; Elbendary, Amira; Shaker, Olfat G.; AlOrbani, Aya M.
Abstract: Background and Objective: New and improved treatment modalities, including lasers and energy‐based devices, are promising treatment options for hypertrophic scars. This study aimed to assess the efficacy and safety of fractional microneedle radiofrequency (FMR) compared with fractional carbon dioxide (CO2 ) laser in the treatment of postburn hypertrophic scars. Patients and Methods: Twenty patients with hypertrophic scars were enrolled in the study. Two areas in each patient were randomly assigned to fractional CO2 laser or FMR. Four sessions, 6–8 weeks apart were performed. The Patient and Observer Scar Assessment Scale (POSAS) was used for clinical evaluation, H & E and orcein‐stained samples were examined for histopathological assessment, and tissue transforming growth factor beta 1 (TGFβ1 ) levels were measured for biochemical evaluation. Results: Both fractional CO2 and FMR‐treated areas showed significant improvement in all parameters 1 month after treatment. Fractional CO2‐treated areas showed a higher degree of improvement compared with FMR in OSAS ( p = 0.025), elastin grading ( p = 0.004), and TGFβ1 levels ( p = 0.000). Patients reported less downtime and showed less postinflammatory hyperpigmentation with FMR compared with fractional CO2, but this did not reach statistical significance ( p = 0.327, p = 0.231; respectively). Conclusion: Our results demonstrate the value of FMR as an effective alternative to fractional CO2 in the treatment of hypertrophic scars, with a potentially favorable safety profile.